PENGARUH GRADASI AGREGAT TERHADAP KARAKTERISTIK CAMPURAN LASTON - Agus Ariawan, I Made; Rai Widhiawati, I.A. (Jurnal Ilmiah Teknik Sipil, 2012)
Damage to roads that often occurs can form cracks, holes, or the sagged; one of the reasons is lack of gradation of aggregate used in accordance with the requirements. The problem is that it is difficult to determine the appropriate proportion aggregate mix gradation in accordance with specifications and there is a lack of understanding of the effect given to the characteristics of the mixture due to the variation obtained in the range of gradation specifications. The research conducted is to examine the characteristics of the variation of the aggregate gradation value, to analyze the characteristics of Laston mixture resulted from aggregate gradation variations, as well as to determine the effect of variation given by aggregate gradation on the characteristics of the Laston. The test results show the characteristics values as follows. Variation 1: Stability is of 1123.87 kg (spec.>750 kg), flow 4.96 mm (spec.>2 mm), MQ 226.59 kg/mm (spec.>180 kg/mm), VMA is of 13.68% that is not meet specifications (spec.>15%), VIM 4.453% (spec. 3%-6%), VFB 67.87% (spec.>63%). Variation 2: Stability is of 1135.37 kg (spec.>750 kg), flow 4.64 mm (spec.>2 mm), MQ 244.76 kg/mm (spec.>180 kg/mm), VMA 15.48% (spec.>15%), VIM 5.122% (spec. 3%-6%), VFB 66.87% (spec.>63%). Ideal Gradation: Stability is of 1143.99 kg (spec.>750 kg), flow of 3.653 mm (spec.>2 mm), MQ 313.21 kg / mm (spec.>180 kg/mm), VMA 16.48% (spec.>15%), VIM 5.901% (spec. 3%-6%), VFB 64.2% (spec.>63%). Variation 3: Stability is of 1160.58 kg (spec.>750 kg), flow 3.49 mm (spec.>2 mm), MQ 333.81 kg/mm (spec.>180 kg/mm), VMA 16.57% (spec.>15%), VIM is 6.06% which has not met the specification (spec. 3%-6%), VFB 63.44% (spec.>63%). Variation 4: Stability is of 1176.51 kg (spec.>750 kg), flow 3.18 mm (spec.>2 mm), MQ 370 kg/mm (spec.>180 kg/mm), VMA 16.81% (spec.>15%), VIM is of 6.359% that has not met the specification (spec. 3%-6%), VFB is of 62.18% that has not also met the specifications (spec.>63%). Base on the analysis of variance, Ftest value for each characteristic of mixture (stability = 13.67, Flow = 104.81, MQ = 73.705, VMA = 14.675, VIM = 4.5138, VFB = 1.352) is greater than the Ftable value ( = 3.48) with an error rate () used is 5%, degrees of freedom treatment is 4 and degrees of freedom random is 10. This proves that with the change in treatment (aggregate gradation variations) makes the differences in the characteristics of the Laston.
Keywords: Laston, Aggregate Gradation, Laston Characteristics.